A Hybrid of Amodiaquine and Primaquine Linked by Gold(I) Is a Multistage Antimalarial Agent Targeting Heme Detoxification and Thiol Redox Homeostasis - Caroline De Souza Pereira; Helenita Costa Quadros; Samuel Yaw Aboagye; Diana Fontinha; Sarah D'Alessandro; Margaret Elizabeth Byrne; Mathieu Gendrot; Isabelle Fonta; Joel Mosnier; Diogo Rodrigo M. Moreira; Nicoletta Basilico; David L. Williams; et al. (MDPI AG, 2022)
Hybrid-based drugs linked through a transition metal constitute an emerging concept for Plasmodium intervention. To advance the drug design concept and enhance the therapeutic potential of this class of drugs, we developed a novel hybrid composed of quinolinic ligands amodiaquine (AQ) and primaquine (PQ) linked by gold(I), named [AuAQPQ]PF6. This compound demonstrated potent and efficacious antiplasmodial activity against multiple stages of the Plasmodium life cycle. The source of this activity was thoroughly investigated by comparing parasite susceptibility to the hybrid's components, the annotation of structure-activity relationships and studies of the mechanism of action. The activity of [AuAQPQ]PF6 for the parasite's asexual blood stages was influenced by the presence of AQ, while its activity against gametocytes and pre-erythrocytic parasites was influenced by both quinolinic components. Moreover, the coordination of ligands to gold(I) was found to be essential for the enhancement of potency, as suggested by the observation that a combination of quinolinic ligands does not reproduce the antimalarial potency and efficacy as observed for the metallic hybrid. Our results indicate that this gold(I) hybrid compound presents a dual mechanism of action by inhibiting the beta-hematin formation and enzymatic activity of thioredoxin reductases. Overall, our findings support the potential of transition metals as a dual chemical linker and an antiplasmodial payload for the development of hybrid-based drugs.